2022
DOI: 10.1097/jsm.0000000000000887
|View full text |Cite
|
Sign up to set email alerts
|

Surfing After Hip Resurfacing Surgery

Abstract: Objective: There is no information about surfing after hip resurfacing arthroplasty (HRA). We did a retrospective study aiming to evaluate the safety and feasibility to resume surfing-an extreme sport with high-impact physical activity-after HRA. Design: Retrospective case series. Setting: Specialist Orthopaedic Group, Mater Hospital Sydney, NSW, Australia. Patients: We evaluated 45 patients who practiced surfing before the onset of pain and hip surgery. Complete clinical and radiographical follow-up and a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Evidence exists that RHA may offer some potential advantages over THA in this sense, including an early return to high-level activities and sports [ 46 ], restoration of native hip biomechanics and decreased proximal femoral stress shielding [ 38 ]. It appears that the potential advantages of RHA could be shown only in the studies that used physical activity-specific outcome measures, as was suggested in the existing literature analyzing the return to sport after RHA [ 33 , 38 , 47 , 48 , 49 ]. As such, well-controlled prospective studies focusing on clinically important differences in patient-reported outcomes and functional results comparing RHA and THA prostheses with modern bearings are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence exists that RHA may offer some potential advantages over THA in this sense, including an early return to high-level activities and sports [ 46 ], restoration of native hip biomechanics and decreased proximal femoral stress shielding [ 38 ]. It appears that the potential advantages of RHA could be shown only in the studies that used physical activity-specific outcome measures, as was suggested in the existing literature analyzing the return to sport after RHA [ 33 , 38 , 47 , 48 , 49 ]. As such, well-controlled prospective studies focusing on clinically important differences in patient-reported outcomes and functional results comparing RHA and THA prostheses with modern bearings are still needed.…”
Section: Discussionmentioning
confidence: 99%